If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(92)*q+(84)(1-q)=(98)*q+(90)(1-q)
We move all terms to the left:
(92)*q+(84)(1-q)-((98)*q+(90)(1-q))=0
We add all the numbers together, and all the variables
92*q+84(-1q+1)-(98*q+90(-1q+1))=0
We add all the numbers together, and all the variables
92q+84(-1q+1)-(98*q+90(-1q+1))=0
We multiply parentheses
92q-84q-(98*q+90(-1q+1))+84=0
We calculate terms in parentheses: -(98*q+90(-1q+1)), so:We add all the numbers together, and all the variables
98*q+90(-1q+1)
We add all the numbers together, and all the variables
98q+90(-1q+1)
We multiply parentheses
98q-90q+90
We add all the numbers together, and all the variables
8q+90
Back to the equation:
-(8q+90)
8q-(8q+90)+84=0
We get rid of parentheses
8q-8q-90+84=0
We add all the numbers together, and all the variables
-6!=0
There is no solution for this equation
| 84+8q=90+8q | | 4=10q | | X=+4-3=2x+2 | | c0=100;c1=0,6;I0=80;T0=75;G0=75 | | 6p-7.6=10.6 | | (2-x)^2=0 | | 2(x^2+x+3)=8(x+1)+2x^2 | | x+¼=⅗ | | 6a-2=19=3 | | 2(xx2+x+3)=8(x-1)+2xx2 | | 7x+1=21x-1 | | 3−3w=6 | | 3−3w= | | 3−3w= 6 | | 2/3*x=7 | | (2x-1)^2+3(2x-1)-4=0 | | 4x=3÷5 | | 5x+4=3x+-2 | | x^2+12^2=(x+8)^2 | | 14-x-5=-5x+3 | | 5x−12=2x−3 | | x(3x-6)(x+1)=0 | | m-1/2=1-m-2/3 | | 8x-6=7x-3 | | 2^7x=8 | | 8x−6=7x−3 | | -0.5x-4=12 | | 6x+34=-6x-24÷4 | | 6d+2×(d÷13)=d×5-5 | | x-2x-x+2=(x-2)(x-1) | | 1274=c/6 | | (2x-1)/10-(3x-3)/5=(2x+3)/15-3 |